2016
DOI: 10.3892/mmr.2016.5656
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 miRNAs sensitize breast cancer stem cells to radiation-induced repression through inhibition of the cyclin D1/Akt1/Wnt1 signaling pathway

Abstract: The tumor-suppressive let-7 family of microRNAs (miRNAs) has been previously identified to induce cell apoptosis, proliferation‑inhibition and suppression of the self‑renewal capacities of cancer stem cells (CSCs). However, let‑7‑mediated sensitization of tumors to radiation treatment remains to be investigated fully in triple negative breast cancer (TNBC), of which the clinical treatment is challenging. The inhibitory effect of let‑7 miRNAs on the self‑renewal ability of CSCs from TNBC was investigated. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 30 publications
1
22
0
3
Order By: Relevance
“…The let-7 family members act as tumor suppressor molecules by binding its target oncogenes, such as HMGA2 ( 51 ), Ras ( 52 ) and c-Myc ( 53 ). Moreover, Sun et al reported that in breast cancer, let-7 directly inhibits cyclin D1 expression, resulting in low phosphorylation of Akt1, which is critical for the let-7 induced inhibition of mammosphere numbers ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…The let-7 family members act as tumor suppressor molecules by binding its target oncogenes, such as HMGA2 ( 51 ), Ras ( 52 ) and c-Myc ( 53 ). Moreover, Sun et al reported that in breast cancer, let-7 directly inhibits cyclin D1 expression, resulting in low phosphorylation of Akt1, which is critical for the let-7 induced inhibition of mammosphere numbers ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…EA, Let-7 ailesi miRNA'ların ifadesini düşürerek meme kanseri kök hücre özelliklerinin korunmasına neden olabilir. Let-7 miRNA'ları siklin D1 ifadesini baskılayarak Akt1'in fosforilasyonunu azaltmaktadır (40). Bu nedenle, Let-7 radyasyon ile indüklenmiş tümör baskılanmasını arttırmaktadır (40).…”
Section: Discussionunclassified
“…Let-7 miRNA'ları siklin D1 ifadesini baskılayarak Akt1'in fosforilasyonunu azaltmaktadır (40). Bu nedenle, Let-7 radyasyon ile indüklenmiş tümör baskılanmasını arttırmaktadır (40). EA'nın Let-7 ailesine ait olgun miRNA'ların ifadelerini düşürmesi ayrıca radyoterapiye karşı direncin oluşmasında da etkili olabilir.…”
Section: Discussionunclassified
“…The abnormal expression of miRNAs is closely related to tumour formation, and certain key factors can promote or inhibit cell proliferation by regulating the pathways thereof ( 13 , 14 ). In addition, miRNAs are involved in regulating migration, metastasis and apoptosis of cells ( 15 – 17 ).…”
Section: Discussionmentioning
confidence: 99%